2016
DOI: 10.1007/s12160-016-9780-1
|View full text |Cite
|
Sign up to set email alerts
|

Stigma Predicts Treatment Preferences and Care Engagement Among Veterans Affairs Primary Care Patients with Depression

Abstract: Background Whereas stigma regarding mental health concerns exists, the evidence for stigma as a depression treatment barrier among patients in Veterans Affairs (VA) primary care (PC) is mixed. Purpose To test whether stigma, defined as depression label avoidance, predicted patients' preferences for depression treatment providers, patients' prospective engagement in depression care, and care quality. Methods We conducted cross-sectional and prospective analyses of existing data from 761 VA PC patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 62 publications
1
22
0
Order By: Relevance
“…However, the majority of studies identified psychological consequences like depression and lowered self-esteem and self-efficacy, social consequences like social isolation, and behavioral consequences like non-disclosure or concealment of one’s condition and impaired self-care behavior. These are all known to ultimately affect people’s utilization of health services, and clinical outcomes of their condition [ 22 , 67 , 68 , 69 , 70 ]. Considering such consequences of stigma identified in this review can severely impact the treatment and management of NCDs [ 71 , 72 ], it is imperative for health policy makers and program managers to focus on reducing NCD-related stigma as a measure to effectively respond to NCDs.…”
Section: Discussionmentioning
confidence: 99%
“…However, the majority of studies identified psychological consequences like depression and lowered self-esteem and self-efficacy, social consequences like social isolation, and behavioral consequences like non-disclosure or concealment of one’s condition and impaired self-care behavior. These are all known to ultimately affect people’s utilization of health services, and clinical outcomes of their condition [ 22 , 67 , 68 , 69 , 70 ]. Considering such consequences of stigma identified in this review can severely impact the treatment and management of NCDs [ 71 , 72 ], it is imperative for health policy makers and program managers to focus on reducing NCD-related stigma as a measure to effectively respond to NCDs.…”
Section: Discussionmentioning
confidence: 99%
“…[28][29][30][31] Reasons cited in previous studies for low levels of treatment initiation-stigma, patient resistance, insufficient training or discomfort of primary care providers, and access barriers, particularly for behavioral health services-likely contributed to the low levels of treatment initiation observed in this study. 32,33 Barriers to treatment initiation specific to primary care settings were also likely contributors. These include greater aversion to depression treatment among primary care patients than behavioral health patients, competing demands, time constraints, and different priorities for patients and providers.…”
Section: Depression Treatment Initiation In Primary Carementioning
confidence: 99%
“…Selfstigmatization in turn leads to more depressive thoughts and shaky selfconfidence (Kao et al, 2016). Consequently, people with depression who tend to stigmatize their own con dition have a higher likelihood of rejecting help from therapists or other treatment approaches (Campbell et al, 2016).…”
Section: Future Researchmentioning
confidence: 99%